Implementation of Argument-Driven Inquiry Learning Model to Enhance Student’s Science Process Skills and Self-Efficacy - Rizka Nurul Dina; Zainuddin Zainuddin; Andi Ulfa Tenri Pada (STKIP Singkawang, 2022)
This study aims to improve students' science process skills and self-efficacy in light wave and optical instruments learning. The research design used was a pretest-posttest control group design. The study population was 8th-grade students of SMP Negeri 8 Banda Aceh, totalling 7 classes. The samples were selected by purposive sampling so that one experimental class and one control class were selected. Data analysis used non-parametric statistics with the Mann-Whitney U test and the calculation of the n-gain score. The results showed that there were significant differences between SPS and self-efficacy students between the implementation of ADI learning model and learning model applied in schools. The n-gain score of SPS and the self-efficacy of the experimental class was higher than the n-gain score of the control class. Therefore, it can be concluded that ADI learning model is effective in enhancing student’s SPS and self-efficacy.